Hubungan Work-Life Balance dengan Psychological Well-Being Pada Ibu yang Bekerja - Leistiawati Hasanah; Sabrina Aulia Pratiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
As more women enter the workforce, many working mothers face dual responsibilities as employees and household managers. Since these demands can affect mental health, the ability to maintain a healthy work-life balance is essential. This study aimed to examine the relationship between psychological well-being and work-life balance among working mothers. The research employed a quantitative approach with a correlational research design. The participants were married working mothers who had children. A purposive sampling technique was used to select the participants. Data were collected using the Ryff Psychological Well-Being Scale and the Fisher Work-Life Balance Scale. Data analysis included validity and reliability testing, assumption testing, correlation analysis, and regression analysis. The findings revealed a positive relationship between work-life balance and psychological well-being among working mothers. Psychological well-being tends to improve when harmony between personal and professional life is achieved. The study concludes that maintaining a balance between work demands and personal life can enhance the psychological well-being of working mothers. Therefore, effective time management, more flexible work policies, and a supportive work environment are needed to promote their psychological well-being.